2016
DOI: 10.2340/00015555-2360
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Apremilast on Pruritus and Skin Discomfort/Pain Correlate With Improvements in Quality of Life in Patients With Moderate to Severe Plaque Psoriasis

Abstract: Pruritus and skin discomfort/pain negatively impact health-related quality of life (HRQoL). The effects of apremilast, an oral phosphodiesterase inhibitor, on pruritus, skin discomfort/pain, and patient global assessment of psoriasis disease activity (PgAPDA) were assessed in moderate/severe chronic plaque psoriasis patients in the phase 3 ESTEEM trials. Significant improvements in pruritus and skin discomfort/pain observed at Week 2 with apremilast versus placebo (both studies, p < 0.0001) were sustained thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 33 publications
2
30
0
2
Order By: Relevance
“…Such clinical data may form an important foundation to support the evidence‐based care of psoriasis patients with itch symptoms. The following discussion reviews the itch effect of topical agents, systemics and biologics, and phototherapy, as revealed in recent studies (Table ) . Itch relief remains a significant gap in the treatment landscape for psoriasis, as not all patients are able to achieve control of this symptom, even with cleared or markedly improved skin.…”
Section: Management Of Itch In Psoriasismentioning
confidence: 99%
“…Such clinical data may form an important foundation to support the evidence‐based care of psoriasis patients with itch symptoms. The following discussion reviews the itch effect of topical agents, systemics and biologics, and phototherapy, as revealed in recent studies (Table ) . Itch relief remains a significant gap in the treatment landscape for psoriasis, as not all patients are able to achieve control of this symptom, even with cleared or markedly improved skin.…”
Section: Management Of Itch In Psoriasismentioning
confidence: 99%
“…The key underlying motor manifestation is caused by a slow and progressive degeneration of dopamine‐producing neurons in the substantia nigra . Parkinson's disease affects 7 to 10 million persons worldwide, making it the second most prevalent neurodegenerative disorder after Alzheimer's disease . Parkinson's disease is also associated with significant economic burden; in 2010, in the United States, medical expenses related to Parkinson's disease were approximately 2‐fold higher than they were for an age‐matched population without Parkinson's disease …”
mentioning
confidence: 99%
“…A recent analysis of the ESTEEM 1 and 2 studies found that apremilast provided rapid and sustained improvement in pruritus and skin discomfort/pain, symptoms not typically captured in psoriasis assessments (e.g. PASI) that contribute significantly to patients’ disease severity and HRQOL perceptions . For example, a significant ( P < 0.001) positive correlation existed between mean changes from baseline in pruritus VAS and DLQI total scores among patients receiving apremilast at Week 16, which was maintained at Week 32 …”
Section: Discussionmentioning
confidence: 99%